1993
DOI: 10.1200/jco.1993.11.6.1014
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Sixth International Society of Pediatric Oncology Wilms' Tumor Trial and Study: a risk-adapted therapeutic approach in Wilms' tumor.

Abstract: Risk-adapted therapy to limit risk of sequelae is possible. More intensive chemotherapy is necessary to prevent abdominal recurrences in nonirradiated stage IIN0 patients treated preoperatively. A three-drug protocol is necessary in stage IIN1 and stage III patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(114 citation statements)
references
References 0 publications
6
99
1
8
Order By: Relevance
“…17 All other countries continued the well established SIOP approach of starting preoperative chemotherapy on the basis of clinical and imaging characteristics consistent with a diagnosis of Wilms' tumour, combined with measuring urinary catecholamines to exclude neuroblastoma, and reserving biopsy for cases with diagnostic dilemma. 2,18,19 Three-dimensional tumour volume was recorded at diagnosis and after completion of preoperative chemotherapy, according to whichever imaging method had been applied (ultrasonography, CT scan, or MRI scan). The calculated volume showed close correlation between methods (appendix).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 All other countries continued the well established SIOP approach of starting preoperative chemotherapy on the basis of clinical and imaging characteristics consistent with a diagnosis of Wilms' tumour, combined with measuring urinary catecholamines to exclude neuroblastoma, and reserving biopsy for cases with diagnostic dilemma. 2,18,19 Three-dimensional tumour volume was recorded at diagnosis and after completion of preoperative chemotherapy, according to whichever imaging method had been applied (ultrasonography, CT scan, or MRI scan). The calculated volume showed close correlation between methods (appendix).…”
Section: Methodsmentioning
confidence: 99%
“…Our data for stage II tumours are similar to a longer-term analysis of outcome of stage II tumours staged after immediate nephrectomy in the NWTSG 4 trial, 27 for which two-drug (vincristine plus actinomycin D) chemotherapy without doxorubicin was the standard after the NWTSG 3 trial. 19 This previous analysis focused on mechanical factors (tumour spill) to stratify stage II patients, whereas our study used in-vivo histological responses and would have placed tumours with spill into stage III. Encouragingly, our data suggest that stage III tumours can be treated eff ectively without doxorubicin, whereas the Children's Oncology Group recommend that tumours with spill should receive doxorubicin.…”
Section: Table 4: Sites Of Relapse In the Intention-to-treat Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the SIOP−2001 protocol, the UMBRELLA protocol continues to recommend preoperative actinomycin D and vincristine for patients newly diagnosed with Wilms tumour aged ≥6 months, based on results of previous SIOP trials that showed tumour downstaging using this regimen 2,6,8,9,14,17 . This benefit was also independently observed in the randomized, controlled UKW3 trial conducted by the UK Children's Cancer and Leukaemia Group (UKCCLG, previously known as the UK Children's Cancer Study Group) 18 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…The sixth SIOP study (conducted between 1980 and 1987), in which patients were treated with preoperative actinomycin and vincristine and postoperative actinomycin and vincristine with or without additional doxorubicin and/or radiotherapy, included only patients with a favourable-histology Wilms tumour (TABLE 1). Some 15 patients with CCSK were included in this study after initial misdiagnosis, but outcomes of these patients were not reported separately 27 . The SIOP 9 study (conducted between 1987 and 1991), including patients with nonmetastatic renal tumours, showed a substantial increase in EFS and OS of patients with CCSK after the addition of an anthracycline (epi rubicin or doxorubicin), an alkylating agent (ifosfamide), and radiotherapy to a dose of 30 Gy (in instances of local stage II and III disease) to the treatment protocol, resulting in a 2-year EFS of 75% and 5-year OS of 88% (n = 16; …”
Section: Siop Trialsmentioning
confidence: 99%